195k views
2 votes

\lim_(x\to \ 0) \frac{√(cos2x)-\sqrt[3]{cos3x} }{sinx^(2) }

User Jay
by
4.6k points

1 Answer

2 votes

Answer:


\displaystyle \lim_(x \to 0) \frac{√(cos(2x)) - \sqrt[3]{cos(3x)}}{sin(x^2)} = (1)/(2)

General Formulas and Concepts:

Calculus

Limits

Limit Rule [Variable Direct Substitution]:
\displaystyle \lim_(x \to c) x = c

L'Hopital's Rule

Differentiation

  • Derivatives
  • Derivative Notation

Basic Power Rule:

  1. f(x) = cxⁿ
  2. f’(x) = c·nxⁿ⁻¹

Derivative Rule [Chain Rule]:
\displaystyle (d)/(dx)[f(g(x))] =f'(g(x)) \cdot g'(x)

Explanation:

We are given the limit:


\displaystyle \lim_(x \to 0) \frac{√(cos(2x)) - \sqrt[3]{cos(3x)}}{sin(x^2)}

When we directly plug in x = 0, we see that we would have an indeterminate form:


\displaystyle \lim_(x \to 0) \frac{√(cos(2x)) - \sqrt[3]{cos(3x)}}{sin(x^2)} = (0)/(0)

This tells us we need to use L'Hoptial's Rule. Let's differentiate the limit:


\displaystyle \lim_(x \to 0) \frac{√(cos(2x)) - \sqrt[3]{cos(3x)}}{sin(x^2)} = \displaystyle \lim_(x \to 0) \frac{(-sin(2x))/(√(cos(2x))) + \frac{sin(3x)}{[cos(3x)]^{(2)/(3)}}}{2xcos(x^2)}

Plugging in x = 0 again, we would get:


\displaystyle \lim_(x \to 0) \frac{(-sin(2x))/(√(cos(2x))) + \frac{sin(3x)}{[cos(3x)]^{(2)/(3)}}}{2xcos(x^2)} = (0)/(0)

Since we reached another indeterminate form, let's apply L'Hoptial's Rule again:


\displaystyle \lim_(x \to 0) \frac{(-sin(2x))/(√(cos(2x))) + \frac{sin(3x)}{[cos(3x)]^{(2)/(3)}}}{2xcos(x^2)} = \lim_(x \to 0) \frac{\frac{-[cos^2(2x) + 1]}{[cos(2x)]^{(2)/(3)}} + \frac{cos^2(3x) + 2}{[cos(3x)]^{(5)/(3)}}}{2cos(x^2) - 4x^2sin(x^2)}

Substitute in x = 0 once more:


\displaystyle \lim_(x \to 0) \frac{\frac{-[cos^2(2x) + 1]}{[cos(2x)]^{(2)/(3)}} + \frac{cos^2(3x) + 2}{[cos(3x)]^{(5)/(3)}}}{2cos(x^2) - 4x^2sin(x^2)} = (1)/(2)

And we have our final answer.

Topic: AP Calculus AB/BC (Calculus I/I + II)

Unit: Limits

User Kschins
by
4.1k points